From p to n type-semiconductor and metallic material: one-step route using femtosecond pulsed laser to produce Ag3VO4/AgVO3/Ag heterostructure - Cruvinel, Guilherme Henrique; Garcia, Rafael de Queiroz; Pinatti, Ivo Mateus; Ribeiro, Renan Augusto Pontes; De Boni, Leonardo; Longo, Elson (Universidade Federal de São Carlos, 2025)
The advent of femtosecond pulsed lasers has revolutionized materials science by enabling intense, ultrashort light pulses, facilitating nonlinear optical phenomena and structural modifications in materials. Ag3VO4, with its narrow band-gap, faces challenges such as charge recombination, leading to the exploration of doped and composite materials to improve efficiency in its applications. This work introduces a femtosecond laser irradiation method to produce intrinsic p-type (Ag3VO4)/n type (AgVO3) semiconductor heterostructures, along with metallic silver (Ag0) with plasmon effect in one-step for the first time. The heterostructures were experimentally characterized (X-ray diffraction, Raman and Ultraviolet-visible spectroscopies, Field Emission Scanning Electron Microscope and Transmission Electron Microscopy) and discussed through quantum-mechanical, which provide insights into their structural, electronic, and vibrational properties and morphological analysis. X-ray diffraction and Raman spectroscopy indicated the presence of metallic Ag and β-AgVO3, with plasmon effects, along with Ag3VO4. A detailed theoretical analysis revealed structural distortions and atomic environment influencing atomic charges, with β-AgVO3 exhibiting more ionic Ag and V cations and significant O atom charge variations compared to Ag3VO4. Unexpected argentophilic and anion-anion interactions in β-AgVO3 were identified, which may help in the understanding of silver nanoparticle growth under electron irradiation. The described production procedure provides the obtention of a new heterostructure, which may have the potential to its applications be explored.
Keywords: Semiconductor; Ag3VO4; Femtosecond pulsed laser; AgVO3; DFT; Plasmon effect; Heterostructure; 9. Indústria, Inovação e Infraestrutura